2020
DOI: 10.1126/sciadv.aaz1114
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight, tough, and sustainable cellulose nanofiber-derived bulk structural materials with low thermal expansion coefficient

Abstract: Sustainable structural materials with light weight, great thermal dimensional stability, and superb mechanical properties are vitally important for engineering application, but the intrinsic conflict among some material properties (e.g., strength and toughness) makes it challenging to realize these performance indexes at the same time under wide service conditions. Here, we report a robust and feasible strategy to process cellulose nanofiber (CNF) into a high-performance sustainable bulk structural material wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 231 publications
(110 citation statements)
references
References 45 publications
(54 reference statements)
3
98
2
Order By: Relevance
“…With regard to structural materials, besides mechanical properties and environmental stability, density is another main factor, determining their practical applications 1 . Based on the low density of both the building blocks and the designed hierarchical nacreous structure, the nacreous bulk material achieved a striking trade-off among density, strength and toughness, which is hard to accomplish simultaneously for engineering structural materials and demonstrates impressive superiority compared with previously reported biomimetic bulk materials ( Figures 4 A and 4B) ( Bouville et al., 2014 ; Chen et al., 2018 ; Estili et al., 2012 ; Gao et al., 2017 ; Grossman et al., 2017 ; Guan et al., 2020a , 2020b ; Le Ferrand et al., 2015 ; Libanori et al., 2013 ; Liu et al., 2013 ; Mao et al., 2016 ; Morits et al., 2017 ; Munch et al., 2008 ; Naglieri et al., 2015 ; Nakagaito et al., 2005 ; Song et al., 2018 ; Yang et al., 2017 ; Zhao et al., 2016 ). As shown in Figure 4 C and Table S2 , the specific strength, (227 MPa/(Mg m −3 )) and specific toughness, (8.4 MPa m 1/2 /(Mg m −3 )) of our nacreous bulk material are both higher than those of the other bulk nacre-mimetics ( Bouville et al., 2014 ; Chen et al., 2018 ; Estili et al., 2012 ; Gao et al., 2017 ; Grossman et al., 2017 ; Guan et al., 2020a ; Le Ferrand et al., 2015 ; Libanori et al., 2013 ; Liu et al., 2013 ; Mao et al., 2016 ; Morits et al., 2017 ; Munch et al., 2008 ; Naglieri et al., 2015 ) ( Song et al., 2018 ).…”
Section: Resultsmentioning
confidence: 87%
“…With regard to structural materials, besides mechanical properties and environmental stability, density is another main factor, determining their practical applications 1 . Based on the low density of both the building blocks and the designed hierarchical nacreous structure, the nacreous bulk material achieved a striking trade-off among density, strength and toughness, which is hard to accomplish simultaneously for engineering structural materials and demonstrates impressive superiority compared with previously reported biomimetic bulk materials ( Figures 4 A and 4B) ( Bouville et al., 2014 ; Chen et al., 2018 ; Estili et al., 2012 ; Gao et al., 2017 ; Grossman et al., 2017 ; Guan et al., 2020a , 2020b ; Le Ferrand et al., 2015 ; Libanori et al., 2013 ; Liu et al., 2013 ; Mao et al., 2016 ; Morits et al., 2017 ; Munch et al., 2008 ; Naglieri et al., 2015 ; Nakagaito et al., 2005 ; Song et al., 2018 ; Yang et al., 2017 ; Zhao et al., 2016 ). As shown in Figure 4 C and Table S2 , the specific strength, (227 MPa/(Mg m −3 )) and specific toughness, (8.4 MPa m 1/2 /(Mg m −3 )) of our nacreous bulk material are both higher than those of the other bulk nacre-mimetics ( Bouville et al., 2014 ; Chen et al., 2018 ; Estili et al., 2012 ; Gao et al., 2017 ; Grossman et al., 2017 ; Guan et al., 2020a ; Le Ferrand et al., 2015 ; Libanori et al., 2013 ; Liu et al., 2013 ; Mao et al., 2016 ; Morits et al., 2017 ; Munch et al., 2008 ; Naglieri et al., 2015 ) ( Song et al., 2018 ).…”
Section: Resultsmentioning
confidence: 87%
“…As one of the most abundant all-green resources on Earth, CNF, a high-performance one-dimensional (1D) nanoscale building block, can be derived from plants or produced by bacteria (Supplementary Fig. 1 ) 23 , 24 . It possesses high strength (at least 2 GPa), a low coefficient of thermal expansion (CTE) (1 × 10 −7 K −1 ), and abundant hydroxyl and carboxyl groups on the surface, indicating it to be an ideal biopolymer matrix for brick-and-mortar structure 24 27 .…”
Section: Resultsmentioning
confidence: 99%
“…1 ) 23 , 24 . It possesses high strength (at least 2 GPa), a low coefficient of thermal expansion (CTE) (1 × 10 −7 K −1 ), and abundant hydroxyl and carboxyl groups on the surface, indicating it to be an ideal biopolymer matrix for brick-and-mortar structure 24 27 . Mica microplatelet, exfoliated from natural mica, is an all-natural two-dimensional (2D) inorganic building block 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, a recent study demonstrated that highperformance bulk structural plates (e.g. 320 mm × 220 mm × 27 mm) can be processed from cellulose nanofibers with light weight, excellent strength and toughness, and high thermal dimensional stability (Guan et al 2020). The assembled plates can be considered as promising substitutes for plastics, ceramics, and metals, making them a strong competitor for the lightweight materials used for automotive and aerospace applications.…”
Section: Nanocellulose and Self-assembled Nanostructuresmentioning
confidence: 99%